2006
DOI: 10.1213/01.ane.0000237311.15294.0e
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and Anesthesia Protocols Used for Magnetic Resonance Imaging Studies in Infants: Provider and Pharmacologic Considerations

Abstract: Most studies report the efficacy of only a single drug to achieve sedation in a broad age range of children. In clinical practice, a variety of sedative and anesthetic regimes are monitored by nurses and physicians. In this study we report the efficacy of a tiered approach to monitoring and sedation in infants. Two-hundred-fifty-eight infants who required magnetic resonance imaging (MRI) studies received either oral chloral hydrate (n = 102) or bolus doses of IV pentobarbital (n = 67) monitored by nurses or IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 18 publications
2
55
0
5
Order By: Relevance
“…Bu durum anestezistleri güvenli, etkin ve erken ambulasyon sağlayan yöntemleri aramaya yöneltmiştir. [7,8] Dalal ve ark.nın [9] 2006 yılında yaptığı çalışmada yenidoğanlara MRG işlemi esnasında sedasyon uygulanmış, 258 yenidoğan çalışmaya alınmıştır. Bizim çalış-mamızda MRG işlemi için hastanın hazır hale gelme süresi propofol grubunda (0.98 dakika) sodyum tiyopental grubuna göre (2.34 dakika) istatistiksel olarak ileri düzeyde anlamlı şekilde kısa bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu durum anestezistleri güvenli, etkin ve erken ambulasyon sağlayan yöntemleri aramaya yöneltmiştir. [7,8] Dalal ve ark.nın [9] 2006 yılında yaptığı çalışmada yenidoğanlara MRG işlemi esnasında sedasyon uygulanmış, 258 yenidoğan çalışmaya alınmıştır. Bizim çalış-mamızda MRG işlemi için hastanın hazır hale gelme süresi propofol grubunda (0.98 dakika) sodyum tiyopental grubuna göre (2.34 dakika) istatistiksel olarak ileri düzeyde anlamlı şekilde kısa bulunmuştur.…”
Section: Discussionunclassified
“…Derlenme süreleri ise sodyum tiyopental grubundaki hastalarda (20.9 dakika) propofol grubundaki hastalara oranla (17.34 dakika) istatistiksel olarak ileri düzeyde anlamlı şekilde uzun bulunmuştur. Bu sonuçlar Dalal ve ark.nın [9] yaptığı çalışmayla uyumludur. Ancak onların derlenme sürelerinin bizim kaydettiğimiz süreler-den çok daha uzun bulunmasının sebebinin onların premedikasyon olarak oral midazolam ve damar yolu açıldıktan sonra iv midozolam vermelerinden kaynaklandığını düşünmekteyiz.…”
Section: Discussionunclassified
“…The optimal delivery of sedation is accomplished by clinician strained in anesthesia. Their experience would allow them to identify and utilize the best available drugs and techniques to full potential to obtain the optimal outcome [6][7][8]10,12,15,19,20]. This would enhance patient safety and also result in studies yielding data with comparable methodologies, skills, and techniques.…”
Section: Proposal For Solutionmentioning
confidence: 99%
“…Moreover, previous studies have indicated that cholinergic neurotransmission plays a role in physical dependence, preference, behavioral sensitization, and sleeping induced by ethanol (Imperato et al, 1998;Jamal et al, 2007;Larsson and Engel, 2004;Nordberg and Wahlstro¨m, 1982;Rothberg et al, 1993;Stancampiano et al, 2004), suggesting the possibility of an interaction between ethanol and arecoline in the central nervous system. Acute administration of pentobarbital can result in sedation, anticonvulsant activity and sleeping or anesthesia (Dalal et al, 2006;Nelson et al, 2002;Uribe-Escamilla et al, 2007). Similar to ethanol, pentobarbital-induced sleeping behavior appears as a loss of the righting reflex (LORR) in mice (Kralic et al, 2003).…”
mentioning
confidence: 99%